2002
DOI: 10.1080/09540120208629664
|View full text |Cite
|
Sign up to set email alerts
|

Drug use, travel and HIV risk

Abstract: A study was conducted to examine the travel experiences of a community sample of 160 drug users and 44 non-users recruited as part of a study of HIV risk. Of the sample, 47% (96/204) reported intercity travel in the previous ten years. Results showed that men were more likely to travel than women, Anglos more than minorities, and young persons more than old. When travellers testing HIV-seropositive (n = 13) were compared with seronegative travellers, HIV-positive travellers reported more sex while travelling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…6,7 In addition, multiple barriers including isolation 7,18 alcohol and illicit drug use 7,16,19 and lack of education 7,8,18 often make accessing help and seeking treatment for BBVs and STIs difficult. Rural workers in our study reported high levels of sexual and drug-related risk behaviour, particularly among the transient group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In addition, multiple barriers including isolation 7,18 alcohol and illicit drug use 7,16,19 and lack of education 7,8,18 often make accessing help and seeking treatment for BBVs and STIs difficult. Rural workers in our study reported high levels of sexual and drug-related risk behaviour, particularly among the transient group.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of sexual debut was 17 years (range [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Sexual Behaviourmentioning
confidence: 99%
“…Given that ordinary life situations may pose risks to these individuals, travel is another dimension of this issue in that it can lead to increased risk of exposure to risky behaviours [11,12]. IDUs face many problems when travelling; these may be due either to their behaviour and habits or to legal institutional, procedural and broader social factors, characteristic of destination countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…Tourists are more likely to engage in risky sexual behaviours whilst travelling than in their own community, [4,7] making it an important area for health promotion [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism constitutes one of the world's largest industries, and travellers can transfer and acquire STIs (sexually transmitted infections) and HIV/AIDS, mainly due to (in)voluntary sexual behaviour [1][2][3][4][5][6]. Tourists are more likely to engage in risky sexual behaviours whilst travelling than in their own community, [4,7] making it an important area for health promotion [8].…”
Section: Introductionmentioning
confidence: 99%